Mof acetyltransferase inhibition ameliorates glucose intolerance and islet dysfunction of type 2 diabetes via targeting pancreatic α-cells. (1st November 2021) - Guo, Xinghong; Cui, Chen; Song, Jia; He, Qin; Zang, Nan; Hu, Huiqing; Wang, Xiaojie; Li, Danyang; Wang, Chuan; Hou, Xinguo; Li, Xiangzhi; Liang, Kai; et al.
Abstract: Background: Previously, we reported that Mof was highly expressed in α-cells, and its knockdown led to ameliorated fasting blood glucose (FBG) and glucose tolerance in non-diabetic mice, attributed by reduced total α-cell but enhanced prohormone convertase (PC)1/3-positive α-cell mass. However, how Mof and histone 4 lysine 16 acetylation (H4K16ac) control α-cell and whether Mof inhibition improves glucose handling in type 2 diabetes (T2DM) mice remain unknown. Methods: Mof overexpression and chromatin immunoprecipitation sequence (ChIP-seq) based on H4K16ac were applied to determine the effect of Mof on α-cell transcriptional factors and underlying mechanism. Then we administrated mg149 to α-TC1-6 cell line, wild type, db/db and diet-induced obesity (DIO) mice to observe the impact of Mof inhibition in vitro and in vivo. In vitro, western blotting and TUNEL staining were used to examine α-cell apoptosis and function. In vivo, glucose tolerance, hormone levels, islet population, α-cell ratio and the co-staining of glucagon and PC1/3 or PC2 were examined. Results: Mof activated α-cell-specific transcriptional network. ChIP-seq results indicated that H4K16ac targeted essential genes regulating α-cell differentiation and function. Mof activity inhibition in vitro caused impaired α-cell function and enhanced apoptosis. In vivo, it contributed to ameliorated glucose intolerance and islet dysfunction, characterized by decreased fasting glucagon and elevated post-challenge insulin levels in T2DM mice. Conclusion: Mof regulates α-cell differentiation and function via acetylating H4K16ac and H4K16ac binding to Pax6 and Foxa2 promoters. Mof inhibition may be a potential interventional target for T2DM, which led to decreased α-cell ratio but increased PC1/3-positive α-cells. Highlights: Mof activates α-cell-specific transcriptional network. Mof-mediated H4K16ac regulates essential genes about α-cells. Mof inhibition leads to enhanced α-cell apoptosis and impaired α-cell function. Mof inhibition ameliorates glucose homeostasis in T2DM mice. Mof inhibition results in decreased α-cell ratio but more PC1/3-positive α-cells.